Incremental cost-effectiveness of trauma service improvements for road trauma casualties: Experience of an Australian major trauma centre - Dinh, M.; Bein, K.; Hendrie, Delia; Gabbe, B.; Byrne, C.; Ivers, R. (CSIRO Publishing, 2015)
Objective. The aim of the present study was to estimate the cost-effectiveness of trauma service funding enhancements at an inner city major trauma centre. Methods. The present study was a cost-effectiveness analysis using retrospective trauma registry data of all major trauma patients (injury severity score >15) presenting after road trauma between 2001 and 2012. The primary outcome was cost per life year gained associated with the intervention period (2007–12) compared with the pre-intervention period (2001–06). Incremental costs were represented by all trauma-related funding enhancements undertaken between 2007 and 2010. Risk adjustment for years of life lost was conducted using zero-inflated negative binomial regression modelling. All costs were expressed in 2012 Australian dollar values. Results. In all, 876 patients were identified during the study period. The incremental cost of trauma enhancements between 2007 and 2012 totalled $7.91 million, of which $2.86 million (36%) was attributable to road trauma patients. After adjustment for important covariates, the odds of in-hospital mortality reduced by around half (adjusted odds ratio (OR) 0.48; 95% confidence interval (CI) 0.27, 0.82; P = 0.01). The incremental cost-effectiveness ratio was A$7600 per life year gained (95% CI A$5524, $19 333). Conclusion. Trauma service funding enhancements that enabled a quality improvement program at a single major trauma centre were found to be cost-effective based on current international and Australian standards.